Interaction of zoospores of the green alga ulva with bioinspired micro- and nanostructured surfaces prepared by polyelectrolyte layer-by-layer self-assembly - Cao, Xinyu; Pettitt, Michala E.; Wode, Florian; Arpa Sancet, Maria Pilar; Fu, Jinhong; Ji, Jian; Callow, Maureen E.; Callow, James A.; Rosenhahn, Axel; Grunze, Michael (Advanced functional materials, 2010)
The interaction of spores of Ulva with bioinspired structured surfaces in the nanometer-micrometer size range is investigated using a series of coatings with systematically varying morphology and chemistry, which allows separation of the contributions of morphology and surface chemistry to settlement (attachment) and adhesion strength. Structured surfaces are prepared by layer-by-layer spray-coating deposition of polyelectrolytes. By changing the pH during application of oppositely charged poly(acrylic acid) and polyethylenimine polyelectrolytes, the surface structures are systematically varied, which allows the influence of morphology on the biological response to be determined. In order to discriminate morphological from chemical effects, surfaces are chemically modified with poly(ethylene glycol) and tridecafluoroctyltriethoxysilane. This chemical modification changes the water contact angles while the influence of the morphology is retained. The lowest level of settlement is observed for structures of the order 2 µm. All surfaces are characterized with respect to their wettability, chemical composition, and morphological properties by contact angle measurement, X-ray photoelectron spectroscopy, scanning electron microscopy, and atomic force microscopy.